Current Issues in Molecular Virology Viral Genetics and Biotechnological Applications - Romanowski, Victor (IntechOpen, 2013)
This book is a collection of chapters dealing with examples of RNA and DNA viruses, and issues such as how these gene packages have learnt to take advantage of their hosts, molecular recognition events that hosts may use to counterattack the viruses, and how researchers have developed strategies to use viruses or their parts as tools for different purposes.